2012
DOI: 10.1007/s00228-012-1360-0
|View full text |Cite
|
Sign up to set email alerts
|

Impaired bioavailability and antiplatelet effect of high-dose clopidogrel in patients after cardiopulmonary resuscitation (CPR)

Abstract: The bioavailability of clopidogrel in critically ill patients after cardiopulmonary resuscitation is significantly impaired compared with stable patients. Therefore, other drugs, preferentially administered intravenously, should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 50 publications
1
37
0
1
Order By: Relevance
“…29 It is also possible that hypothermia may delay gastric absorption and reduce the bioavailability of oral antiplatelet agents. 30 Penela et al described that among 16 patients presenting with acute coronary syndromes and cardiac arrest treated with PCI and hypothermia, 5 (31.2%) developed stent thrombosis within 30 days. 31 Conversely, in a consecutive series of 1334 patients with STEMI undergoing PCI, hypothermia in 75 cardiac arrest patients was not associated with an increased rate of stent thrombosis compared with control.…”
Section: Results Of the Current Study: Safetymentioning
confidence: 99%
“…29 It is also possible that hypothermia may delay gastric absorption and reduce the bioavailability of oral antiplatelet agents. 30 Penela et al described that among 16 patients presenting with acute coronary syndromes and cardiac arrest treated with PCI and hypothermia, 5 (31.2%) developed stent thrombosis within 30 days. 31 Conversely, in a consecutive series of 1334 patients with STEMI undergoing PCI, hypothermia in 75 cardiac arrest patients was not associated with an increased rate of stent thrombosis compared with control.…”
Section: Results Of the Current Study: Safetymentioning
confidence: 99%
“…Bjelland et al showed that after therapeutic hypothermia the effect of clopidogrel is non-existent in the first day of treatment and during the third day the recovery in partial [63]. Also there is evidence that bioavailability of clopidogrel is reduced in hemodynamic unstable patients after successful cardio-pulmonary resuscitation [64].…”
Section: Mechanisms For Anti-platelet Drugs Resistance In Critically mentioning
confidence: 99%
“…The paper by Souckova et al on the bioavailability of clopidogrel used during therapeutic hypothermia (TH) following cardiopulmonary resuscitation excellently illustrates this point, as only two of nine hypothermic patients showed adequate platelet inhibition. This was due to both delayed clopidogrel absorption and reduced bioavailability [2]. In the discussion of their findings, Souckova et al could have lent further support for their conclusion by citing a previous larger study on clopidogrel efficacy during TH after cardiac arrest [3].…”
mentioning
confidence: 93%